Consciência fonológica e fonema : discutindo seus conceitos e seus empréstimos - Souza, érika Costa de (2011)
This paper reflects on the conceptual issues regarding the notion of phonological awareness as a prerequisite for the acquisition of written language and the concepts of phoneme and sound. Despite repeatedly being used by researches in the areas of language pathology, the terms phoneme and sound have constantly been regarded as two equal entities, which implies in theoretical and methodological consequences in the research in these fields. The appropriation of these terms from Linguistics, in the phonological awareness researches was discussed in this dissertation based on the theoretical constructs of Structural Linguistics, especially those prepared by the precursors of the area of Phonology, as Trubetzkoy and Jakobson, and the American linguist Edward Sapir. Their reflections served as a conceptual support to confront the "appropriation" of the terms from Linguistics and the theoretical commitment maintained by the areas of language disorders with their original concepts. This work originated from theoretical reflections on the data from an experiment conducted with deaf and hearing children, students from 1st to 3rd grade of elementary school, whose aim was to evaluate the phonological awareness based on a copy activity of monosyllabic and trisyllabic words and pseudo-words. The initial concepts that guided the study, as well as the point of view of theories about phonological awareness and its assumption as a pre-requisite for the acquisition of an alphabetic written language, were confronted with the support of the Linguistics.